APPLYING CONSTRUCTIVIS APPROACHES TO ENHANCE CREATIVITY LEARNING ACHIEVEMENT - Nenny Triyana; Turdjai Turdjai (DIADIK, 2019)
This study aimed to describe the application of the synectic model in learning IPA can improve creativity of students in the fourth model in learning IPA can imprive student achievementin class V SDN Gugus III Kab. Lebong city describes the effectivess of synopitic model improve the learning achievement of math student in grade V SDN 73 Gugus III Lebong.The research is a classroom action research combined with quasi experiments. The subjects of this research are grade V A and B SDN 73 Lebong City as PTK class and experimen class white class V B SDN 73 as control class. The instruments cllas used are observation and test sheets. The technique of data analysis using the formula of the average percentage value of data analysis using the formula of the average percentage value of classical leaaning and t tes, white the observation data is analyzed with the average score, highest, score, score difference and the range of values for each criterion.